Youth sports specialization and musculoskeletal injury: a systematic review of the literature - Fabricant, P. D.; Lakomkin, N.; Sugimoto, D.; Tepolt, F. A.; Stracciolini, A.; Kocher, M. S. (The Physician and Sportsmedicine, 2016)
Objectives: Early sports specialization is being seen with increasing frequency in children and adolescents in an attempt to achieve elite performance status. This phenomenon has attracted negative medical and lay media attention due, in part, to the possibility of an increased risk of acute and overuse injuries. The purpose of this study was to systematically review available research on youth sport specialization and musculoskeletal injury.